Cover Picture: The Effect of Cholesterol on Membrane Dynamics on Different Timescales in Lipid Bilayers from Fast Field‐Cycling NMR Relaxometry Studies of Unilamellar Vesicles (ChemPhysChem 3/2014). Issue 3 (24th February 2014) - Fraenza, Carla C.; Meledandri, Carla J.; Anoardo, Esteban; Brougham, Dermot F.
<x xml:space="preserve">Abstract</x> The cover image shows NMR relaxation data for cholesterol‐doped liposomes. The contributions from the different dynamic modes are highlighted in colour. Analysis by D. F. Brougham and E. Anoardo et al. shows that the non‐cholesterol lipids can be partitioned into affected (ordered) and unaffected populations, with three ordered lipids to each cholesterol over a range of concentrations, as shown on p. 425.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>